2018
DOI: 10.1136/bmjinnov-2018-000288
|View full text |Cite
|
Sign up to set email alerts
|

Designing the landscape for technological development in neonatal neurocritical care

Abstract: ObjectivesTo identify current ‘gaps’ in clinical practice or therapeutic knowledge of the care of neonatal neurointensive care patients and to determine the impact healthcare technologies can have on improving outcomes.DesignThe Cambridge Institute for Manufacturing’s (IfM) roadmapping methodology.SettingCambridge, UK.Participants16 delegates were selected through professional networks. They provided coverage of academia and clinical skills, as well as expertise in neonatology, engineering and technology devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…While there is strong evidence that adults with acute neurological conditions benefit from a specialized neurocritical care, the impact of such care in the neonatal population is less clear [ 8 , 46 ]. However, emerging evidence suggests its potentially positive impact on neurodevelopmental outcome [ 24 , 31 , 46 48 ]. Glass et al demonstrated that the rate of epilepsy after acute symptomatic neonatal seizures was lower in a cohort of newborns managed by a neonatal neurocritical care service [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is strong evidence that adults with acute neurological conditions benefit from a specialized neurocritical care, the impact of such care in the neonatal population is less clear [ 8 , 46 ]. However, emerging evidence suggests its potentially positive impact on neurodevelopmental outcome [ 24 , 31 , 46 48 ]. Glass et al demonstrated that the rate of epilepsy after acute symptomatic neonatal seizures was lower in a cohort of newborns managed by a neonatal neurocritical care service [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first step in the development of our NNCUs was the encouragement of the parent-infant bonding time [ 24 ]. Our ultimate goal was to have neuro-NICU available to the parents for 24 hours, but as the first step, we aimed to arrange for a comfortable overnight stay for the mother.…”
Section: Methodsmentioning
confidence: 99%